2015
DOI: 10.1186/s11671-015-1082-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cutting parameters on the depth of subsurface deformed layer in nano-cutting process of single crystal copper

Abstract: Large-scale molecular dynamics simulation is performed to study the nano-cutting process of single crystal copper realized by single-point diamond cutting tool in this paper. The centro-symmetry parameter is adopted to characterize the subsurface deformed layers and the distribution and evolution of the subsurface defect structures. Three-dimensional visualization and measurement technology are used to measure the depth of the subsurface deformed layers. The influence of cutting speed, cutting depth, cutting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Figure 7 indicates that there is a transition of material removal mechanisms from plowing to cutting with the increase of DOC. The observed DOC-dependent material removal mode is in agreement with previous studies [ 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 92%
“…Figure 7 indicates that there is a transition of material removal mechanisms from plowing to cutting with the increase of DOC. The observed DOC-dependent material removal mode is in agreement with previous studies [ 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 92%
“…4a and Fig. 4d To further quantitatively explore the generation of SSD layer in micro-machining of titanium alloy, the effect of cutting speed on dislocation morphologies was investigated in Fig 5. In comparison to previous MD studies, whose cutting speed stayed around 18000 m/min [37], the predictions matched well with actual operations. Results indicated that the subsurface microstructure exhibited hypersensitivity to increased cutting velocity.…”
Section: Resultssupporting
confidence: 76%
“…However, most of these simulations usually adopt defect-free monocrystalline structures as the work material [3][4][5][6][7][8][9]. On the other hand, most engineering materials exist in polycrystalline forms and mechanical properties such as flow stress, yield stress and hardness of metals and alloys [10,11] dramatically scale with grain size.…”
Section: Introductionmentioning
confidence: 99%